Construction of Meaning of the Undergraduate Course in Business Administration by High and Low Income Students - Marcelo de Rezende Pinto; Marcos Eugênio Vale Leão; Ramon Silva Leite; Danielle Ramos de Miranda Pereira (BBR: Brazilian Business Review)
This paper reports the results of an empirical study undertaken with a sample of 368 undergraduate business administration students from five private universities in a large Brazilian city. The objective was to analyze the differences in perceptions of the course by students from high and low income backgrounds regarding the following issues: the cultural and symbolic elements involving higher education; the relevance of higher education in consumer priorities and the influence on consumption behavior of students; the appropriateness of the course to their reality; and the expected benefits of obtaining a degree. The data were analyzed using the Grade of Membership (GoM) and t-test statistical techniques. The results, which were compared with the theoretical framework on consumption in a cultural and symbolic perspective, signaled there is a difference in meaning between the two groups of students.